1998
DOI: 10.1001/archfami.7.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Religious Commitment and Health Status: A Review of the Research and Implications for Family Medicine

Abstract: The empirical literature from epidemiological and clinical studies regarding the relationship between religious factors (eg, frequency of religious attendance, private religious involvement, and relying on one's religious beliefs as a source of strength and coping) and physical and mental health status in the areas of prevention, coping, and recovery was reviewed. Empirical studies from the published literature that contained at least 1 measure of subjects' religious commitment and at least 1 measure of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
124
1
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(134 citation statements)
references
References 52 publications
3
124
1
6
Order By: Relevance
“…This should be investigated in future studies, but our finding does both identify another high-risk group and suggest that intervention may be strategically delivered via the workplace. Consistent with the cross-national literature (Bazargan, Sherkat, and Bazargan, 2004;Galen and Rogers, 2004;Matthew et al, 1998), religious involvement was associated with lower prevalence of hazardous use of all substances. Religion may operate as a protective factor by discouraging drinking and improving coping and social support (Koenig, 2001).…”
Section: Discussionsupporting
confidence: 85%
“…This should be investigated in future studies, but our finding does both identify another high-risk group and suggest that intervention may be strategically delivered via the workplace. Consistent with the cross-national literature (Bazargan, Sherkat, and Bazargan, 2004;Galen and Rogers, 2004;Matthew et al, 1998), religious involvement was associated with lower prevalence of hazardous use of all substances. Religion may operate as a protective factor by discouraging drinking and improving coping and social support (Koenig, 2001).…”
Section: Discussionsupporting
confidence: 85%
“…The literature is abundant with studies indicating a positive association between religious involvement and health or between spirituality and well-being among dying patients. [1][2][3][4][5][6][7][8] Pediatricians whose beliefs mirrored this literature were more likely to make SR inquiries and more likely to experience patient SR requests. Several studies have also found that most patients (in nonpediatric settings) want their physicians to be able to respond to SR issues, particularly patients with strong SR orientation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Research has documented positive relationships between religious behavior and health, [2][3][4][5][6][7][8] and the majority of patients seem to want their physicians to be able to address the SR aspects of the illness experience. 9 -11 Although many physicians accept the idea that patient religiousness or spirituality can positively affect health, most do not initiate SR inquiry with patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…R elationships between spirituality and mortality have been investigated in medical populations but remain controversial (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Variable associations have been found depending on definitions of spirituality and patient populations studied (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%